Perlindungan Hukum Data Pribadi Pasien Untuk Mencegah Kebocoran Di Media Sosial - Audina Sukmawan, Yulia; Kartika Mantasti Hapsari, Restiana; Damayanti, Dwi; Aisya Awanis, Saraya (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
In the current digital era, the amount of information shared through social media continues to increase, including patient data that is vulnerable to leakage caused by healthcare workers who use social media in their professional activities and during data collection. This situation poses risks of privacy violations and legal issues. Law No. 17 of 2023 concerning Health does not yet provide sufficient protection for patient data, as it lacks explicit provisions regarding criminal sanctions. This study examines the appropriate legal standards for protecting patients' personal data in Indonesia to address these issues. The main objective of this research is to analyse criminal sanctions for healthcare workers who disclose patients' personal information through social media. The legal gap in the current health law, which does not specifically regulate criminal sanctions for breaches of patient data privacy, is the core subject of this study. The legal analysis conducted in this research is expected to strengthen legislation related to patient privacy protection and assist health authorities in preventing the misuse of patient information on social media by medical and healthcare personnel in hospitals.